Pengaruh Waktu Reaksi Terhadap Viskositas Dan Densitas Tetraetil Ortosilikat Dari Silika Abu Sekam Padi - Mujiyanti, Dwi Rasy; Nisa, Hayatun; Rosyidah, Kholifatu; Ariyani, Dahlena; Abdullah, Abdullah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Tetraethyl Ortosylicate (TEOS) is a material is widely used in industrial fields. One source of silica (SiO2) is rice husk ash. In this study was determined the effect of reaction time on viscosity and density in making TEOS from silica rice husk. Silica resulting from the purification of rice husk ash is used in the TEOS manufacturing process by examining the variation of reaction time. One mole of ethanol and 0.25 mole of silica powder were added into 250 ml of round bottom flask followed by the addition of 1 gram of CuO/Al2O3 catalyst then the mixture was refluxed for 30, 35, 40, 45 and 50 hours with sufficient stirring and a temperature of 90 Â°C. The FTIR characterization results show that there are three main functional groups, namely the -OH, Si-O and C-O groups in the five TEOS synthesis results. Wavenumbers of the â€“OH functional groups obtained ranged from 3349 cm-1 - 3315 cm-1; Si-O functional groups range from 813 cm-1 - 606 cm-1 and C-O functional groups range from 1105 cm-1 - 1040 cm-1. Reaction time has no significant effect on viscosity. Reaction time has no significant effect on the density and density of the resulting TEOS.